Formation of the foundations of foreign policy activities for conducting interstate relations - Usmonov Bakhtiyor Botirovich (Genius Journals, 2023)
The leadership of Uzbekistan from the first days of gaining independence, showed great concern for an active multilateral foreign policy that meets the national interests of the country. At the same time, based on the strategy, principles and priority areas of foreign policy, Uzbekistan began to pay great attention to the establishment of international relations on an equal basis and the development of bilateral cooperation with almost all countries of the world community
Keywords: community; cooperation; countries; international